A graphical user interface for XCAT phantom configuration, generation and processing. (20th January 2017) - Myronakis, Marios E; Cai, Weixing; Dhou, Salam; Cifter, Fulya; Hurwitz, Martina; Segars, Paul W; Berbeco, Ross I; Lewis, John H
Abstract: The main aim of this work is to facilitate generation of the extended cardiac and torso (XCAT) phantom with focus on automated and simplified generation of four-dimensional computed tomography (4DCT) simulated images. A comprehensive graphical user interface (GUI) was developed to expedite phantom generation, processing and 4DCT image generation. The use of irregularly shaped patient-specific tumors with the XCAT phantom, a capability that is not implemented in the current version of the application, was also addressed. XCAT phantoms were generated to demonstrate the GUIs functionality. The following GUI functions were demonstrated; (a) generation of 4DCT images using respiratory motion signal; (b) generation of maximum intensity image from 4DCT images; (c) insertion of irregularly shaped tumors from DICOM files; (d) exporting XCAT data to DICOM format and importing to an Eclipse treatment planning system. An open source, publicly available graphical interface for the XCAT phantom was developed. The graphical interface is capable of generating a wide variety of phantoms to simulate 4DCT acquisition images. The graphical interface is also able to incorporate irregularly shaped tumors within the XCAT framework. The graphical interface is freely distributed for imaging research.